If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -14 = p Reorder the terms: -14 + 3p = p Solving -14 + 3p = p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -14 + 3p + -1p = p + -1p Combine like terms: 3p + -1p = 2p -14 + 2p = p + -1p Combine like terms: p + -1p = 0 -14 + 2p = 0 Add '14' to each side of the equation. -14 + 14 + 2p = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 2p = 0 + 14 2p = 0 + 14 Combine like terms: 0 + 14 = 14 2p = 14 Divide each side by '2'. p = 7 Simplifying p = 7
| 18=2t+8 | | -3x-3=-2x-2 | | x^2-88=-7 | | 0.09xX=123.42 | | 11x+21=6x+11 | | p/7=28 | | 15x+50=9x+32 | | 2(3x-4)=7(2x+5) | | 3-(x+2)=1 | | -r/3≤6 | | 28=p/7 | | -20x+24=-12x+16 | | -12x+63=-8x+39 | | -9x+69=-6x+45 | | t-22.4=34.8 | | -77=-9a-5 | | 11x-32=7x-20 | | X-4-5=0 | | -21x-125=-14x-69 | | X+5x=21+15+3x | | 3x=5x+3+10 | | -4x+6=-2x+4 | | (3/8)-(2/10) | | (X-a)/(x-b) | | -19x-149=-12-86 | | 10x-32=6x-16 | | 2+3u=17 | | 0.09xX=67.87 | | 2(4x+9)-8x= | | 11x+110=6x+70 | | x-5=x+23 | | 7-3/4=x |